Creative Thinking Ability of Junior High School Students in Solving Open-Ended Problems on Plane Geometry - Ardiansyah, Dicky; Siswono, Tatag Yuli Eko; Harini, Novita Vindri; Heng, Limalin (Journal of the Indonesian Mathematics Education Society, 2025)
This study aims to analyze the creative thinking abilities of Junior High School students in solving open-ended mathematical problems. Creative thinking ability is an essential aspect of mathematics, particularly when solving problems that require varied solutions. This research employs a descriptive qualitative approach involving five seventh-grade students. Data were collected through open-ended problem-solving tests and interviews. The analysis was conducted by identifying indicators of creative thinking, such as fluency, flexibility, and novelty, based on students’ responses. The results show that students’ creative thinking abilities vary. Some students were unable to produce multiple different solutions (flexibility). Elaborating on their answers also posed a challenge for 60% of the students. This study provides implications for the development of mathematics learning that emphasizes enhancing students’ creative thinking abilities through open-ended problems.